2015
DOI: 10.2147/dddt.s79563
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle albumin-bound paclitaxel (nab-paclitaxel) as second-line chemotherapy in HER2-negative, taxane-pretreated metastatic breast cancer patients: prospective evaluation of activity, safety, and quality of life

Abstract: BackgroundA prospective, multicenter trial was undertaken to assess the activity, safety, and quality of life of nanoparticle albumin-bound paclitaxel (nab-paclitaxel) as second-line chemotherapy in HER2-negative, taxane-pretreated metastatic breast cancer (MBC).Patients and methodsFifty-two women with HER2-negative MBC who were candidates for second-line chemotherapy for the metastatic disease were enrolled and treated at three centers in Northern Italy. All patients had previously received taxane-based chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 62 publications
3
32
0
1
Order By: Relevance
“…The hereby reviewed data confirm that sensorial neuropathy occurs late in the course of treatment with both the qw and q3w schedules, also in taxane-pretreated patients, and adequate management by dose reductions or treatment delays allows to maintain an adequate dose-intensity of the drug [Gradishar et al 2005[Gradishar et al , 2009Blum et al 2007;Von Minckwitz et al 2013;Palumbo et al 2015aPalumbo et al , 2015b.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The hereby reviewed data confirm that sensorial neuropathy occurs late in the course of treatment with both the qw and q3w schedules, also in taxane-pretreated patients, and adequate management by dose reductions or treatment delays allows to maintain an adequate dose-intensity of the drug [Gradishar et al 2005[Gradishar et al , 2009Blum et al 2007;Von Minckwitz et al 2013;Palumbo et al 2015aPalumbo et al , 2015b.…”
Section: Discussionmentioning
confidence: 54%
“…Similarly, a strong association between caveolin-1 expression and breast carcinomas with a basal-like phenotype has been reported, suggesting that the utilization of the gp60/caveolin-1 pathway as a means to deliver cytotoxic therapy may be particularly lucrative in some breast cancer subtypes [Pinilla et al 2006;Savage et al 2007] and that patients with higher caveolin-1 expression, such as those with a basallike phenotype, may derive greater benefit from nab-paclitaxel [Altundag et al 2006]. On the other hand, retrospective and real-life data showed a significantly higher ORR in patients with visceral-dominant metastases treated with nab-paclitaxel compared with solvent-based paclitaxel [O'Shaughnessy et al 2013;Palumbo et al 2015aPalumbo et al , 2015b. Thus, disease-related factors such as visceral-dominant metastases may be clinical predictive markers of treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that single-agent nab-paclitaxel 260 mg/m 2 every 3 weeks is an effective and well-tolerated regimen as second-line chemotherapy in HER2-negative, taxane-pretreated MBC, and that it produced interesting values of ORR and PFS without the concern of significant toxicity [35]. For example, a prospective, multicenter trial was conducted to assess the activity and safety of nab-paclitaxel as second-line chemotherapy in HER2-negative, taxane-pretreated MBC [36]. The ORR was 48%, and the overall CBR was 77%.…”
Section: Discussionmentioning
confidence: 99%
“…Vinorelbine has been widely employed in pretreated breast cancer, either in its intra-venous or oral formulation, yielding response rates ranging from 10% to 35% [18,19]. Additional agents include nab-paclitaxel, which in two phase II trials yielded a response rate of 15% and 48% respectively in taxane pre-treated patients [20,21]. Ixabepilone, was quite active in heavily pre-treated patients, with a 18.5% response rate, however, because of its relevant neurotoxicity, observed in 63% of the patients, was not approved by EMA [22][23][24].…”
Section: Discussionmentioning
confidence: 99%